1993
DOI: 10.3109/10641969309037110
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Channel Blockers in Current Medical Practice: An Update for 1993

Abstract: Calcium channel blocking drugs (CCB) have been used to lower blood pressure since 1970. Three classes are currently available, the phenylalkylamines, the benzothiazepines, and the dihydropyridines. The structure of the L-type, voltage dependent calcium channel has been elucidated with molecular techniques and the different binding sites of the various CCB described. CCB have specific effects at the site of target organs. In the kidney, all classes produce natriuresis. Their action appears independent of the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 42 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…The study indicated that dihydropyridine could improve the laying performance and decrease hepatic fat and abdominal fat in laying hens (Zou et al, 2007). Furthermore, dihydropyridine, as a calcium channel blocker or calcium antagonist, is the effective drug in curing cardiovascular diseases in humans, including angina, hypertension, myocardial ischemia, cardiac failure and atherosclerosis (Luft and Haller, 1993;Zhang, 1996). However, there is no report on the regulation of lipid metabolism by dihydropyridine in broiler chickens.…”
mentioning
confidence: 99%
“…The study indicated that dihydropyridine could improve the laying performance and decrease hepatic fat and abdominal fat in laying hens (Zou et al, 2007). Furthermore, dihydropyridine, as a calcium channel blocker or calcium antagonist, is the effective drug in curing cardiovascular diseases in humans, including angina, hypertension, myocardial ischemia, cardiac failure and atherosclerosis (Luft and Haller, 1993;Zhang, 1996). However, there is no report on the regulation of lipid metabolism by dihydropyridine in broiler chickens.…”
mentioning
confidence: 99%